Analisis Pengembangan Desa Wisata untuk Keberlanjutan Petani Strawberry di Desa Wisata Pandanrejo Menggunakan Metode Participatory Rural Appraisal (PRA) - Deti Rahmawati; Soedarso Soedarso; Arfan Fahmi (JURNAL SOSIAL HUMANIORA (JSH), 2023)
The concept of Village-City Development's hegemony is being clarified in various media outlets, necessitating periodic reviews to strike a balance between the two. The harmonization of village development is evident in the rapid improvement and transformation of villages, exemplified by the emergence of tourist villages. Among these, Pandanrejo Tourism Village stands out, offering strawberry barn tourism that has been operational since late 2018. This tourism destination not only showcases strawberry gardens and products but also provides educational tours related to strawberries. To support the success of tourism villages, efforts can be made by mapping the community's potential and needs, which will inform the development programs aimed at empowering the local populace. The research undertaken in this study employed the Participatory Rural Appraisal (PRA) method, which ensures that the people of Pandanrejo Tourism Village are not mere recipients of top-down programs, but active participants in designing bottom-up development initiatives. This approach encourages the community's involvement throughout the development process. The study encompasses several stages of analysis, allowing village communities to actively participate in identifying social problems and their root causes, devising solutions, and subsequently formulating programs. These programs will receive budgetary support and be implemented based on principles of cooperation, empowerment, and community independence